Penerapan Layanan Konseling Kelompok Melalui Dzikir Ratib Al Haddad Dalam Mengatasi Kenakalan Remaja - Nasrullah; Suryati; Hartika Utami Fitri (Journal of Society Counseling, 2023)
This study examines the "Implementation of Group Counseling Services Through Dzikir Ratib Al Haddad in Overcoming Juvenile Delinquency". This study aims first, to find out the Technical Description of the Application of Group Counseling Services Through Dhikr Ratib Al Haddad in Overcoming Juvenile Delinquency. Second, to find out the inhibiting factors for implementing Group Counseling Services Through Dzikir Ratib Al Haddad in Overcoming Juvenile Delinquency. This study uses a qualitative method. With data collection techniques including observation, interviews and documentation. Furthermore, with data analysis techniques through reduction, presentation and drawing conclusions. The results showed first, the implementation of counseling activities was well regulated based on the stage of implementation of counseling services with members understanding the meaning and purpose of group counseling opening dzikir al haddad material prioritizing gentleness and a good approach to religious (religious) activities for adolescents. Transitional or transitional stage: the implementation of counseling services sees that adolescent family members can recognize their own emotional state, control emotions. Stages of activity: Providing religious education from an early age is very important for children, so that when they reach adulthood they can control themselves, and their behavior and even their minds become more alert and they don't just do things. The final stage: reading Dhikr Al Haddad facing the Qibla, in a state of ablution. Second, the supporting factor is the ability of the ustad or companion who is able and masters the Islamic Religion sciences so that in providing dzikir coaching to teenagers, the synergy between the accompanying teenagers as congregations and also the surrounding community is very helpful in the process of progress and independence of the Ratib Al Haddad Dhikr Council as well as the success of various kinds of activities, as well as the patience shown by the Ustadz in dealing with teenagers who violate their attitudes and behavior. Meanwhile, the inhibiting factors were only the limited time for carrying out the study and the delay in attending the youth so that some were not effective in receiving material that had been carried out for quite a long time.